2017
DOI: 10.1016/j.celrep.2017.07.011
|View full text |Cite
|
Sign up to set email alerts
|

CFP1 Regulates Histone H3K4 Trimethylation and Developmental Potential in Mouse Oocytes

Abstract: Trimethylation of histone H3 at lysine-4 (H3K4me3) is associated with eukaryotic gene promoters and poises their transcriptional activation during development. To examine the in vivo function of H3K4me3 in the absence of DNA replication, we deleted CXXC finger protein 1 (CFP1), the DNA-binding subunit of the SETD1 histone H3K4 methyltransferase, in developing oocytes. We find that CFP1 is required for H3K4me3 accumulation and the deposition of histone variants onto chromatin during oocyte maturation. Decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
88
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 39 publications
2
88
0
Order By: Relevance
“…What influence does lower H3K4me3 have on the oocyte? In murine oocytes, decreased H3K4me3 level has been linked to misexpression of genes essential for meiotic resumption, leading to failure to maturation (Xu, Chen et al, ; C. Yu et al, ). Consistent with its role in promoting oocyte maturation, increased H3K4me3 was associated with improving meiotic and developmental competence of porcine oocytes (X. X. Yu et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…What influence does lower H3K4me3 have on the oocyte? In murine oocytes, decreased H3K4me3 level has been linked to misexpression of genes essential for meiotic resumption, leading to failure to maturation (Xu, Chen et al, ; C. Yu et al, ). Consistent with its role in promoting oocyte maturation, increased H3K4me3 was associated with improving meiotic and developmental competence of porcine oocytes (X. X. Yu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…What influence does lower H3K4me3 have on the oocyte? In murine oocytes, decreased H3K4me3 level has been linked to misexpression of genes essential for meiotic resumption, leading to failure to maturation (Xu, Chen et al, 2017;C. Yu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the importance of epigenetic modification in regulating somatic cell reprogramming as well as early embryo development has been widely reported (Liu et al, ; Matoba & Zhang, ; Yu et al, ). However, only a handful of studies have indicated that epigenetic modification plays an important role in controlling oocyte PCD during PF pool establishment (Sun et al, , ).…”
Section: Introductionmentioning
confidence: 99%